Impact of Mono‐Fluorination on the Photophysics of the Flavin Chromophore. (5th May 2018) - Reiffers, Anna; Torres Ziegenbein, Christian; Engelhardt, Alyn; Kühnemuth, Ralf; Gilch, Peter; Czekelius, Constantin
Abstract: Three mono‐fluorinated derivatives of the flavin core system 10‐methyl‐isoalloxazine (MIA) were synthesized. Aqueous solutions of these compounds were characterized by steady‐state and time‐resolved spectroscopy. The positions for the fluorination (6, 7 and 8) were motivated by the nodal structure of the frontier orbitals of MIA. In comparison with MIA, the fluorination results in bathochromic (6F‐ and 7F‐MIA) and hypsochromic (8F‐MIA) shifts of the adiabatic excitation energy of the lowest allowed transition. Shifts of up to 500 cm −1 were observed. These spectroscopic shifts go along with changes in fluorescence quantum yields and lifetimes. In addition, triplet yields are affected. For 7F‐MIA, a 50% increase in the fluorescence quantum yield as well as a 50% decrease in triplet yield is observed rendering the compound interesting for fluorescence applications. The measured effects are discussed in terms of qualitative perturbation theory. Abstract : The depicted mono‐fluorinated flavin derivatives were synthesized. Fluorination affects their photo‐physical properties, for instance their fluorescence lifetimes.